Asynchronous Hydroclimatic Modeling for the Construction of Physically Based Streamflow Projections in a Context of Observation Scarcity - Ricard, Simon; Sylvain, Jean-Daniel; Anctil, François (Frontiers in Earth Science, 2020)
Asynchronous hydroclimatic modelling is proposed for the construction of physically based streamflow projections over regions characterized by meteorological observation scarcity. The novel approach circumvents the requirement for meteorological observations by 1) calibrating quantile mapping transfer functions simultaneously to the parameters of the hydrologic model, 2) forcing the hydrologic model with post-processed climate simulations, and 3) intentionally ignoring the correlation between simulated streamflow values and observations. As a result, relative humidity, solar radiation and wind speed are integrated to a full hydroclimatic modelling chain, allowing the construction of streamflow projections forcing the Penman-Montheith reference evapotranspiration formulation over a forested catchment that flows into the St-Lawrence River, Canada. Results confirm a more accurate simulated hydrological response relative to a conventional hydroclimatic modelling chain employing reanalyses as description of the climate system. They also highlight the contribution to uncertainty in streamflow projections from biased climate variables issued by the reanalyses. The suggested framework assumes the hydrologic regime as a functional proxy to corresponding climate drivers. We believe the latter opens promising perspectives in the scope of producing more reliable estimations of water-related and energy-driven processes such as streamflow generation, snow accumulation and melt, river ice jams, water temperature, or vegetation growth under evolving climate conditions.